2009
DOI: 10.1111/j.1476-5381.2009.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the regional haemodynamic effects of intermedin (adrenomedullin 2) compared with adrenomedullin in conscious rats

Abstract: Background and purpose: Intermedin (IMD) is a newly identified member of the calcitonin family of peptides that shares structural and functional homology with adrenomedullin (AM). In vivo cardiovascular effects of AM have been described, but relatively little is known of the in vivo actions of IMD. The purpose of this study was to compare the regional haemodynamic effects of IMD with those of AM in conscious rats, and investigate possible underlying mechanisms. Experimental approach: Measurements of blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…30,45 NO mediates the effects of IMD in the PVN on the RSNA and MAP in 2K1C rats and peripheral vasodilatation. 6,28,29,38 In this study, our results showed that non-selective NOS inhibitor L-NAME prevented IMD-induced decrease in the CSAR and IMD microinjection into the PVN significantly increased NO content in 2K1C, 38 which indicates that IMD may activate NO-producing neurons and increase NO production in the PVN, and that NO, in turn, decreases the CSAR.…”
Section: Discussionsupporting
confidence: 56%
“…30,45 NO mediates the effects of IMD in the PVN on the RSNA and MAP in 2K1C rats and peripheral vasodilatation. 6,28,29,38 In this study, our results showed that non-selective NOS inhibitor L-NAME prevented IMD-induced decrease in the CSAR and IMD microinjection into the PVN significantly increased NO content in 2K1C, 38 which indicates that IMD may activate NO-producing neurons and increase NO production in the PVN, and that NO, in turn, decreases the CSAR.…”
Section: Discussionsupporting
confidence: 56%
“…The i.v. infusion of ADM2/IMD 1–47 increases the blood flow and decreases the vascular resistance of the heart, lungs, kidneys, liver, stomach, small intestine, adrenal glands and testes (Fujisawa et al , ), more potently than ADM (Jolly et al , ). The modified cardiac function, vasodilation, renal function and neuroendocrine effect are involved in the haemodynamic regulation by ADM2 (Figure ).…”
Section: Cardiovascular Effects Of Adm2mentioning
confidence: 99%
“…ADM2 has a hypotensive effect, but the potency comparisons have produced variable results. The overall rank of the hypotensive potency is ADM2/IMD 1–53 > ADM > ADM2/IMD 1–47 = CGRP > ADM2/IMD 1–40 , which can be blocked by CGRP receptor antagonist (Roh et al , ; Taylor et al , ; Jolly et al , ). However, other studies have reported a different potency ranking for the hypotensive effect: ADM2/IMD 1–47 = ADM2/IMD 1–40 ≥ ADM = ADM2/IMD 1–53 (Takei et al , ; Pan et al , ; Fujisawa et al , ; Ren et al , ).…”
Section: Cardiovascular Effects Of Adm2mentioning
confidence: 99%
“…IMD had a negative inotropic effect on the isolated myocardium because of NO-cGMP pathway activation with concomitant thin myofilament desensitization by increased cTnI phosphorylation [25], which provides a coherent explanation for the previously reported contradictory results (positive or negative inotropic effect). In conscious rat models, the regional haemodynamic profile of IMD resembled that of ADM [30], and some of the vasodilator effects of IMD were mediated by ADM receptors and NO but not by K(ATP) channels. Using anaesthetic rat models, Abdelrahman et al found that IMD dose-dependently decreased mean arterial pressure and increased heart rate; the depressive effect of IMD was not mediated via the L-arginine-NO pathway, production of prostanoids or opening of tetraethylammonium-sensitive K + channels but was opposed by activity of the sympathetic nervous system [33].…”
Section: Distribution and Production Of Imdmentioning
confidence: 91%
“…IMD treatment increased the activity of NO synthase (NOS) and content of NO in tissues and augmented the uptake of L-arginine by cells [29]. NO activates GC and elevates intracellular cGMP levels for multiple effects such as vasodilation, anti-oxidative stress, and inhibition of cell apoptosis [8,30,31]. IMD153 significantly increased NO production and endothelial NOS (eNOS) activity in rat aortas and was more potent than equivalent ADM [32].…”
Section: Distribution and Production Of Imdmentioning
confidence: 99%